2011
DOI: 10.1089/dia.2010.0214
|View full text |Cite
|
Sign up to set email alerts
|

Needle with a Novel Attachment Versus Conventional Screw-Thread Needles: A Preference and Usability Test Among Adults with Diabetes and Impaired Manual Dexterity

Abstract: Background: NovoTwist Ò (Novo Nordisk A/S, Bagsvaerd, Denmark) is an insulin pen needle that features a novel attachment and detachment system. The aim of this test was to assess overall preference and handling of NovoTwist compared with conventional screw-thread needles in people with type 1 or type 2 diabetes. Methods: One hundred twenty adults with type 1 or type 2 diabetes and manual dexterity dysfunction who were currently self-injecting with an insulin pen were included in this open-label, randomized, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…This usability test showed that significantly more children and adolescents had an overall preference for NovoTwist needles compared with screw-thread needles. The findings of this study are in agreement with three other studies [12][13][14] of NovoTwist in adults, which showed that adults with diabetes preferred NovoTwist for ease of use, 12 ease of attachment, 12,13 and ease of detachment 12 compared with conventional screw-thread needles. Similarly, in this study, most children and adolescents also found NovoTwist the easiest needle to use, easier to attach, and easier to detach than screw-thread needles.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This usability test showed that significantly more children and adolescents had an overall preference for NovoTwist needles compared with screw-thread needles. The findings of this study are in agreement with three other studies [12][13][14] of NovoTwist in adults, which showed that adults with diabetes preferred NovoTwist for ease of use, 12 ease of attachment, 12,13 and ease of detachment 12 compared with conventional screw-thread needles. Similarly, in this study, most children and adolescents also found NovoTwist the easiest needle to use, easier to attach, and easier to detach than screw-thread needles.…”
Section: Discussionsupporting
confidence: 92%
“…12 The participants' response to NovoTwist in this study is encouraging, as it is a novel needle attachment system that the patients had no previous experience with, compared with screw-thread needles that the patients may have used since initiating their insulin regimens. Seven out of eight parents of children who required assistance in their daily treatment stated that they would be very likely to allow their children to attach NovoTwist.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Moreover, the simplicity of pen use is particularly important not only to older patients suffering from impaired manual dexterity and tremors, but also for younger individuals who are too busy to devote much time to their injections. 16 , 17 Insulin pens are portable, thus they offer greater flexibility in day-to-day living especially in younger patients. Lee et al in another study looked at the quality-of-life improvement when shifting to insulin pens in 65 patients.…”
Section: Introductionmentioning
confidence: 99%